Femtosecond laser written ZBLAN tilted fibre Bragg grating for mode-locked mid-infrared laser applications - Theodosiou, A.; Henderson-Sapir, O.; Kalli, Kyriacos (My University, 2023)
Tilted fibre Bragg gratings (TFBGs), especially ones with a tilt angle of 45o, are very promising and effective fibre elements that can act as polarizing elements Therefore, a TFBG in conjunction with an isolator, a coupler and polarisation control can creat an all-fibre mode-locked laser. A TFBG is based on the Brewster angle principle, which couples out of the fibre the s-polarisation of the light while maintaining the transmission of p-polarisation through the fibre core with minimal losses. In other words, the 45o-TFBGs are behaving as in-fibre polarisers. Compared with other types of polarisers TFBGs have a higher polarisation extinction, low insertion loss, broadband responsivity, wavelength tunability and, can be adapted to any type of fibres. Moreover, from a fibre laser perspective, TFBGs being an all-in-fibre components, do not require coupling in and out of the fibre or collimation within the laser resonators, resulting in more robust and stable fibre laser systems, with minimal maintenance. In this paper we describe our recent progress on developing high polarising and low loss tilted fibre Bragg grating. The grating is inscribed in a ZBLAN passive fibre for potential use as a polarising element for future mid-infrared mode-locked laser. The inscription was performed using the plane-by-plane method utilising femtosecond pulses at 517 nm. The polarising elements were characterised in transmission in terms of polarisation dependent loss, transmission loss and bandwidth. The results show significantly improved characteristics compared to previous works and is a significant step towards a monolithic mode-locked mid-infrared lasers at the 3.5 µm band.
Keywords: femtosecond laser inscription; in-fibre polarisers; mid-IR fiber lasers; tilted fiber Bragg gratings; ZBLAN